Improved lattice‐based mix‐nets for electronic voting - Valeh Farzaliyev; Jan Willemson; Jaan Kristjan Kaasik (IET Information Security, 2023)
Abstract Mix‐networks were first proposed by Chaum in the late 1970s–early 1980s as a general tool for building anonymous communication systems. Classical mix‐net implementations rely on standard public key primitives (e.g., ElGamal encryption) that will become vulnerable when a sufficiently powerful quantum computer will be built. Thus, there is a need to develop quantum‐resistant mix‐nets. This article focuses on the application case of electronic voting where the number of votes to be mixed may reach hundreds of thousands or even millions. We propose an improved architecture for lattice‐based post‐quantum mix‐nets featuring more efficient zero‐knowledge proofs while maintaining established security assumptions. Our current implementation scales up to 100,000 votes, still leaving a lot of room for future optimisation.